PENGEMBANGAN PANDUAN PRAKTIKUM BERBASIS ANDORID - Agustina, Putri; Santoso, Handoko; Widowati, Hening (BIOLOVA, 2022)
The learning process in higher education, especially biology education, cannot be separated from practicum activities. The process of practicum activities with various observations of course requires a proper practicum guide so that the development of a microtechnical practicum guide is needed. The practical guide accompanied by the android system is expected to help students to more easily carry out practicum activities. Of course, these studies require a valid theoretical study to support scientific work to be better. This paper aims to describe the understanding of theory, the different forms of theory, the role and function of theory, as well as theory building techniques, including the practical ability to produce citations in theoretical research using methods and methods of citing references and this paper aims to find out that the development of an android-based practicum guide can be used as a reference. learning media by examining various articles that have been published.